Operational amplifier noise : techniques and tips for analyzing and reducing noise - Kay, Art (Newnes, 2012)
Arthur Kay's exciting new publication is a must have for practicing, professional electrical engineers. This comprehensive guide shows engineers how to design amplifiers and associated electronics to minimize noise, providing tricks, rules-of-thumb, and analysis to create successful low noise circuits. Forget the classical textbook traps of equations, virtual grounds, and a lot of double-speak, the novel but educational presentation used here uses definition-by -example and straight-forward analysis. This is the ultimate reference book for engineers who don't have the time to read, since th.